Study of spatiotemporal variation and driving factors of habitat quality in the northern foothills of the Qinling Mountains: a case study of Xi’an, China - Ma, Ling; Wang, Chuanming; Wang, Liyang; Jin, Shumeng; Kou, Xiaomei (Frontiers in Ecology and Evolution, 2023)
This study aimed to analyze spatiotemporal changes in Xi 'an section of the northern foothills of the Qinling Mountains from 1990 to 2020. Temporal and spatial changes in habitat quality in the study area were visualized using InVEST model and land use data, and factors affecting habitat quality were analyzed using Geo-detector. The results showed that during the study period, the cultivated land, grassland, and water decreased by 16.40%, 74.37%, and 35.39%, respectively, while the area of forest land and construction land increased, among which the construction land increased by 117.70%, the largest increase, and the forest land increased by 8.47%. The main changes in land use are the conversion of cultivated land into forest land and construction land, and the conversion of 2 This is a provisional file, not the final typeset article grassland into forest land and cultivated land. During the period 1990-2020, the average habitat quality index in the study area changed from 0.8617 to 0.8585, showing a slow decreasing trend. The spatial distribution of habitat quality showed a trend of "high in the south, moderate in the north, and low in the northwest". The high habitat quality was mainly concentrated in the southern forest land, the middle habitat quality was mainly distributed in the northern cultivated land, and the low habitat quality was mainly distributed in the northwest construction land. The land use type has a great influence on habitat quality, and the interaction between any two factors is stronger than that of a single factor. The temporal and spatial variation of habitat quality is influenced by both natural and human factors.